Peningkatan Kinerja Guru dalam Pembelajaran di Kelas Melalui Supervisi Klinis di SD Negeri 005 Bengkong Kota Batam Tahun Ajaran 2017/2018 - Sukarni Sukarni (Journal on Education, 2022)
The role of teacher performance in the teaching process is very important, where the teacher is the leader in a learning setting in the classroom. The role of the teacher as a professional educator is expected to be an example or role model for other students and teachers in advancing a better education. Educators are expected to understand and implement components as educators, namely pedagogic, personality, professional and social so that the learning process is in line with our goals as educators. Good educators can not be separated from the many roles in them including the role of students, administrative staff, teachers and school principals, so from the importance of thorough monitoring so that it can run according to its main duties and functions which is in accordance with the title of the research I took, namely "Improving Teacher Performance in Learning in Classes at SDN 005 Bengkong Batam City Academic Year 2017/2018 "from the research I did, the results from 6 teachers showed that the first cycle showed 71.98% and the second cycle 92.44% it could be categorized as very good. Based on the results of the research above, the Research on Improving Teacher Performance in Learning Through Clinical Supervision in Classrooms at SDN 005 Bengkong Batam City for the 2017/2018 Academic Year is feasible to apply.